A comparative study of quality of life in patients with papillary thyroid carcinoma undergoing microwave ablation vs. Total thyroidectomy - Yan Li; Sheng-Nan Huo; Nai-Cong Lu; Li-li Peng; Ying Wei; Zhen-Long Zhao; Ming-an Yu (International Journal of Hyperthermia, 2023)
AbstractObjective To compare the health-related quality of life (HRQoL) of patients with T1N0M0 papillary thyroid carcinoma (PTC) who underwent microwave ablation (MWA) and those who underwent total thyroidectomy (TT).Materials and methods From February 2018 to February 2022, 180 T1N0M0 PTC patients were enrolled in present study, including 90 in the MWA group and 90 in the TT group, respectively. The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) and Thyroid Cancer-Specific Quality of Life Questionnaire (THYCA-QoL) were completed by patients to evaluate their HRQoL scoresResults According to the results of the EORTC-QLQ-C30, there was a significant difference in the scores of global health, physical, emotional, etc. between the two groups, which indicated that the quality of life in these items in the MWA group was better than those in the TT group (all p < 0.05). According to the results of the THYCA-QoL, all items had significant differences between the two groups except for headache, which demonstrated the thyroid-specific quality of life was higher in the MWA group than in the TT group (all p < 0.05).Conclusion Ultrasound (US)-guided MWA offers a significant advantage in HRQoL over TT in T1N0M0 PTC patients, which provides an important reference for MWA as an alternative strategy to TT.